2019
DOI: 10.1111/jgh.14660
|View full text |Cite
|
Sign up to set email alerts
|

The suppressive role of HYAL1 and HYAL2 in the metastasis of colorectal cancer

Abstract: Background Hyaluronidases (HAases), enzymes that degrade hyaluronan, have been widely investigated in cancer biology. However, whether HAases serve as tumor promoters or suppressors has been controversial in different cancers, and the exact role of HAases in colorectal cancer (CRC) has not been elucidated. Methods The expression levels of HYAL1, HYAL2, and HYAL3 in cancer and corresponding normal tissues from CRC patients were examined via immunohistochemistry. Then the correlation between HAases levels and pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 31 publications
2
12
0
Order By: Relevance
“…26 Typically, MMP2 and MMP9 mediate degradation of tumor extracellular matrix, and overexpression of these crucial regulators has been reported to facilitate metastasis of malignant tumors. 27 In our present study, transwell migration assay and wound healing assay revealed that DHM remarkably suppresses the invasion and migration of CRC cell lines. Moreover, expression of MMP2 and MMP9 was found to markedly decrease with increasing doses of DHM.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…26 Typically, MMP2 and MMP9 mediate degradation of tumor extracellular matrix, and overexpression of these crucial regulators has been reported to facilitate metastasis of malignant tumors. 27 In our present study, transwell migration assay and wound healing assay revealed that DHM remarkably suppresses the invasion and migration of CRC cell lines. Moreover, expression of MMP2 and MMP9 was found to markedly decrease with increasing doses of DHM.…”
Section: Discussionsupporting
confidence: 56%
“…It has been widely established that migration and invasion are key factors affecting the treatment of various cancers, and are also leading cause of high mortality associated with CRC 26 . Typically, MMP2 and MMP9 mediate degradation of tumor extracellular matrix, and overexpression of these crucial regulators has been reported to facilitate metastasis of malignant tumors 27 . In our present study, transwell migration assay and wound healing assay revealed that DHM remarkably suppresses the invasion and migration of CRC cell lines.…”
Section: Discussionsupporting
confidence: 53%
“…Concerning renal cell carcinoma (RCC), TIMP2 is inversely correlated with markers of tumour progression [ 55 ]. However, TIMP2 is a poor prognostic marker in gastric cancer [ 56 ], in contrast to its role in colorectal cancer [ 57 ]. TIMP2 is involved in glioma inhibition by different drugs as an intermediate link in the upregulated expression in different studies [ 58 , 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…In one previous research, Yan et al ( 59 ) have established a CD133-related gene signature for predicting glioblastoma prognosis; the CD133-related signature successfully distinguishes GBM from LGG, and the CD133-related gene signature defines a new subtype of GBM with shorter survival time. In colorectal cancer, high expression of HYAL1 and HYAL2 can inhibit tumor metastasis ( 60 ), but in triple-negative breast cancer, high expression of HYAL2 genes is associated with shorter disease-free survival, higher tumor recurrence rate, and higher tumor metastasis rate ( 61 ). MMP2 is involved in the invasion of thyroid tumor cells, and its expression is regulated by the ERK and JNK pathways ( 62 , 63 ).…”
Section: Discussionmentioning
confidence: 99%